Study of conservative treatment in uncomplicated acute appendicitis - Gedam, B. S.; Gujela, Ajit; Bansod, Prasad Y.; Akhtar, Murtaza (International Surgery Journal, 2017)
Background: Management of acute appendicitis with antibiotics only, without surgery is currently evaluated. Non-operative management of uncomplicated acute diverticulitis and salpingitis has been well established but the non-operative management of acute appendicitis remains controversial. Growing evidence indicates that patients with acute uncomplicated appendicitis can be treated safely with an antibiotics- first approach. Methods: A tertiary care hospital based longitudinal study with duration of 26 month. Patients with clinical and radiological feature of acute appendicitis presenting within 48 hours of initiation of abdominal pain with Modified Alvarado Score ≥5 included. Various demographic, clinico-pathological, radiological factors were studied. Results: 71 patients evaluated, mean age of 30.45±9.71 years. Tenderness in RIF was the commonest finding followed by Fever and rebound tenderness. Leucocytosis seen in 74.65% Modified Alvarado score of 5-6 was present in 18.32% whereas 7-9 was present in 81.68% patients. USG was suggestive of appendicitis in 84.50% patients. Conservative treatment was successful in 74.65% patients with no treatment failure. 25.35% patients, conservative treatment failed. Overall recurrence was seen in 13.11% cases that were successfully managed during primary admission. Conclusions: Majority of cases of first attack of uncomplicated acute appendicitis can be treated successfully by conservative treatment. However, conservative treatment requires monitoring and repeated re-evaluation to identify failure which needs to be treated promptly by surgery. Treatment failure on primary admission as well as the short- term recurrence after conservative treatment is low and acceptable. The outcome of conservative treatment does not depend on Modified Alvarado Score.